Antimicrobial chitosan nanodroplets: new insights for ultrasound-mediated adjuvant treatment of skin infection. (June 2015) - Banche, Giuliana; Prato, Mauro; Magnetto, Chiara; Allizond, Valeria; Giribaldi, Giuliana; Argenziano, Monica; Khadjavi, Amina; Gulino, Giulia Rossana; Finesso, Nicole; Mandras, Narcisa; Tullio, Vivian; Cavalli, Roberta; et al.
ABSTRACT : Background: Chronic wounds, characterized by hypoxia, inflammation and impaired tissue remodeling, are often worsened by bacterial/fungal infections. Intriguingly, chitosan-shelled/decafluoropentane-cored oxygen-loaded nanodroplets (OLNs) have proven effective in delivering oxygen to hypoxic tissues.Aim: The present work aimed at investigating nanodroplet antimicrobial properties against methicillin-resistant Staphylococcus aureus (MRSA) or Candida albicans, toxicity on human keratinocytes (HaCaT) and ultrasound (US)-triggered transdermal delivery.Materials & methods : Nanodroplet antibacterial/antifungal properties, human cytotoxicity, and US-triggered transdermal delivery were measured through microbiological, biochemical, and sonophoresis assays, respectively.Results: OLNs and oxygen-free nanodroplets (OFNs) displayed short- or long-term cytostatic activity against MRSA or Candida albicans, respectively. OLNs were not toxic to keratinocytes, whereas OFNs slightly affected cell viability. Complementary US treatment promoted OLN transdermal delivery.Conclusion: As such, US-activated chitosan-shelled OLNs appear as promising, nonconventional and innovative tools for adjuvant treatment of infected chronic wounds.